TOLERANSI SENGON BUTO (Enterolobium cyclocarpum Griseb) YANG DITANAM PADA MEDIA LIMBAH TAILING TERCEMAR SIANIDA DENGAN PERLAKUAN PUPUK - Syarif, Fauzia (BERITA BIOLOGI, 2008)
Sengon buto (Enterolobium cyclocarpum Griseb) is one of the potential plant species for land reclamation and possibly for phytoremediation because of its fast growing even on poor soil, and its ability to fertilize soil through nitrogen fixation. For phytoremediation purpose we need fast growing plant with high ability to absorp target contaminant. Fertilization is needed to improve plant growth. This experiment was carried out to study the tolerance of sengon buto (Enterolobium cyclocarpum Griseb) grown on cyanide contaminated tailing media on various level of NPK fertilizer.The sengon buto seed were planted in the tailing of gold mine media mixed with compost (4:1) in pots. Various levels of NPK fertilizer were applied i.e. 0, 2, 4, 6, 8 g/pot at 2 and 2.5 month after planting (MAP).The plant were harvested at 6 MAP. The result showed that NPK fertilizer increase plant growth at level 2 of 2 g/pot, however the value of the increment was not significantly different with control plant (0 g/pot). Cyanide content of NPK treated plants were higher than the untreated plants. The highest value of shoot/root cyanide content ratio was on the NPK untreated plants (4.34) followed by 2 g/pot treatment (3.59). It is means that sengon buto is potential for phytoremediation of tailing of gold mining.